(untitled) (American International Journal of Supply Chain Management, 2021)
The Covid-19 (coronavirus) crisis is severe, and will have a horrendous financial and economic effect on all over the world. Consequently, this pandemic has jeopardized the rising economy of Bangladesh. The country’s economy largely depends on Ready-made Garments, remittances, and export of agricultural products. In response to this unusual ‘Great Recession’, Bangladesh is exploring the use of technologies to fight back this recession amidst the ongoing social distancing, self-isolation and travel limitations. This study critically analyzes and explores the financial policies adapted by the Bangladesh government. The study identifies that the government is applying Keynesian approach and providing adequate incentives and subsidies in order to strengthen the economy. In addition, the study draws insight into how the government is spending a significant amount on Information and Communication Technology (ICT) and popularizing ICT platforms to uphold financial activities. It also elaborates on the implications of a huge government budget in several sectors through ICT. However, the government slightly misuses the budget by allying with corruption and money laundering. Finally, the study successfully advocates that, although the Keynesian approach invites issues like debt, inflation, and unemployment but the government prefers the Keynesian approach (direct assistance or subsidies from the government) to protect Bangladesh economy.